Outcomes of patients with stroke treated with thrombolysis according to prestroke Rankin Scale scores - Gumbinger, Christoph; Ringleb, Peter A.; Ippen, Franziska M.; Ungerer, Matthias; Reuter, Björn; Bruder, Ingo; Daffertshofer, Michael; Stock, Christian (Neurology, 2019)
It is common practice to withhold IV thrombolysis (IVT) for acute ischemic stroke in patients with preexisting disabilities. To test the hypothesis of an association of IVT and good clinical outcome also in patients with preexisting disabilities without an increase in mortality, we analyzed data from 52,741 patients (15,317 treated with IVT) depending on prestroke Rankin Scale (pRS) score.
Gesehen am 09.03.2020